2008
DOI: 10.1007/s10856-008-3505-3
|View full text |Cite
|
Sign up to set email alerts
|

The anatase phase of nanotopography titania plays an important role on osteoblast cell morphology and proliferation

Abstract: The surface properties of biomaterials play a vital role in cell morphology and behaviors such as cell adhesion, migration, proliferation and differentiation. Three different crystal phases of titania film (rutile, anatase and amorphous titania) with similar roughness were successfully synthesized by DC reactive magnetron sputtering. The surface roughness of each film was about 8-10 nm. Primary rat osteoblasts were used to observe changes in morphology and to evaluate cell behavior at the film surface. The num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
132
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(149 citation statements)
references
References 32 publications
7
132
2
Order By: Relevance
“…The quasi-amorphous oxides can be crystallized by heating, which explains why anatase was found in the group 2 of implants, since it was subjected to an anodizing process. The manufacturer of this group has not disclosed, but an annealing is done after anodizing in order to obtain the anatase phase, because it has some biological advantages: the anatase phase of titania film enhances osteoblast adhesion, proliferation and differentiation by affecting surface contact angles and/or wettability 36 .…”
Section: Xrd Analysismentioning
confidence: 99%
“…The quasi-amorphous oxides can be crystallized by heating, which explains why anatase was found in the group 2 of implants, since it was subjected to an anodizing process. The manufacturer of this group has not disclosed, but an annealing is done after anodizing in order to obtain the anatase phase, because it has some biological advantages: the anatase phase of titania film enhances osteoblast adhesion, proliferation and differentiation by affecting surface contact angles and/or wettability 36 .…”
Section: Xrd Analysismentioning
confidence: 99%
“…Since the surface roughness of CFRC was not significantly changed by the coating with the carbon-titanium layer, the beneficial effects of this coating on cell colonization could be explained by spontaneous oxidation of Ti and C in the cell culture system, including the formation of titanium oxides and oxygen-containing chemical functional groups. These features are known to enhance cell adhesion and growth (He et al, 2008;Sawase et al, 2008) and attract phosphate and calcium ions (Toworfe et al, 2006;Rakngarm et al, 2008), which facilitate bone tissue formation and bonding between the artificial implant and bone. Interestingly, the improvement of cell colonization by the C:Ti film was more pronounced in VSMC than in MG 63 cells, which was probably due to a different sensitivity of low-passaged cells and cell line to the physicochemical properties of the material surface.…”
Section: Amorphous Carbonmentioning
confidence: 99%
“…This is only to be expected, because the main mineral component of bone is a complex inorganic calcium phosphate system called apatite 37) . It has been suggested that cell morphology with a fully spreading shape and a regular cytoskeleton enables better cell proliferation and differentiation 38) . Figure 8a showed there was no statistically significance on proliferation before 3 days between group E2 and group C. After day 5, group E2 had significantly higher (p<0.05) cell proliferation.…”
Section: Discussionmentioning
confidence: 99%